2021
DOI: 10.3389/fonc.2021.608932
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of CLEC11A Predicts Favorable Prognosis in Acute Myeloid Leukemia

Abstract: BackgroundAcute myeloid leukemia (AML) is a heterogeneous disease of the hematopoietic system, for which identification of novel molecular markers is potentially important for clinical prognosis and is an urgent need for treatment optimization.MethodsWe selected C-type lectin domain family 11, member A (CLEC11A) for study via several public databases, comparing expression among a variety of tumors and normal samples as well as different organs and tissues. To investigated the relationship between CLEC11A expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Although the biological function of CLEC11A has not been revealed in CRC, several studies have reported that CLEC11A is significantly associated with the clinical outcomes of cancer patients. [24,25] The prognostic value of CYRAB has been demonstrated in CRC. [26,27] In addition, CYRAB can promote the invasion and metastasis of CRC via the regulation of the epithelial-mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
“…Although the biological function of CLEC11A has not been revealed in CRC, several studies have reported that CLEC11A is significantly associated with the clinical outcomes of cancer patients. [24,25] The prognostic value of CYRAB has been demonstrated in CRC. [26,27] In addition, CYRAB can promote the invasion and metastasis of CRC via the regulation of the epithelial-mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of CKLF1-related pathways can enhance the anti-tumor e cacy of cisplatin and reduce the nephrotoxicity induced by cisplatin [37,38]. Yin C et al found that CLEC11A was highly expressed in AML and associated with a favorable outcome [39]. High levels of CLEC11A DNA methylation were found in patients with poor prognosis, and DNA methylation affected gene expression, suggesting that inhibition of DNA methylation may be used to treat AML [40].…”
Section: Discussionmentioning
confidence: 99%
“…CLEC11A-expressing lung cancer cells have been shown to promote the growth of tumors in mice while inhibition of CLEC11A expression prevented tumor growth [ 12 ]. Interestingly, Yin and colleagues recently reported that increased methylation of CLEC11A , corresponding to decreased gene and protein expression, led to poor survival in AML patients [ 13 ]. These conflicting reports indicate that further studies are needed to elucidate the role of CLEC11A in cancer, with specific attention to the role of methylation.…”
Section: Introductionmentioning
confidence: 99%
“…Survival rates incorporate many different factors: the age of patients, type of chemotherapy, stage of cancer, race, gender, and time from diagnosis to treatment [ 4 ]. While previous studies showed a relationship between CLEC11A and survival, these other factors were not considered specific to methylation of CLEC11A [ 12 , 13 ]. Therefore, the goal of this study was to examine the relationship between CLEC11A methylation, staging, genetic risk factors, and demographic data to determine whether CLEC11A can be used as a prognostic factor in AML patients.…”
Section: Introductionmentioning
confidence: 99%